1993
DOI: 10.1002/chp.4750130403
|View full text |Cite
|
Sign up to set email alerts
|

Changing clinical practice: Which interventions work?

Abstract: Changing clinical practice is a complex challenge. A framework is presented for integrating the perspectives of continuing education, technology assessment, and quality assurance. The effectiveness of cwrent interventions is reviewed. We describe what is known about practice determinants, the most important of which are physician age, clinical training, knowledge, skill, personal characteristics, practice setting, arid reimbursement policies. The rehtive importance of these factors varies and seems to be condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 95 publications
0
16
0
1
Order By: Relevance
“…However, the recently completed Canadian study of family physicians' practices related to driving assessment of the elderly used a questionnaire that was rigorously developed and pilot tested (9). We created a slightly modified version and selected variables according to a framework that classified potential factors affecting clinical practices into predisposing, enabling, and reinforcing factors (11). When creating new questions, we followed Dillman's guidelines on writing questions (12).…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…However, the recently completed Canadian study of family physicians' practices related to driving assessment of the elderly used a questionnaire that was rigorously developed and pilot tested (9). We created a slightly modified version and selected variables according to a framework that classified potential factors affecting clinical practices into predisposing, enabling, and reinforcing factors (11). When creating new questions, we followed Dillman's guidelines on writing questions (12).…”
Section: Measurement Of Variablesmentioning
confidence: 99%
“…There is literature that suggests that merely providing information to physicians may result in only minimal effect on practice behavior Lomas 1991). Others have found that more effective methods for effecting change involves communication, peer pressure, and education (Adelson et al 1997;Tamblyn and Battista 1993). Changing physician practice behavior requires an active process of psychoeducation, ongoing prompts, active supervision and involvement in process, and auditing to assure adherence to procedures (Avorn and Soumerai 1983;Davis et al 1995).…”
Section: Discussionmentioning
confidence: 97%
“…The ultimate evaluation of any educational intervention or product in medicine is to demonstrate a change in clinical practice. There is evidence to suggest that in general CME works well in improving physician competence and generally less well in changing practice performance (Tamblyn & Battista, 1993;Wensing & Grol, 1994).…”
Section: Rule 7: the Content And Tasks Must Stimulate Analytic Skillsmentioning
confidence: 99%